2021
DOI: 10.21203/rs.3.rs-450017/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of Educational Intervention Based on Self-Efficacy Theory on The Caring Behavior of Mothers Having Children with Cancer

Abstract: Background Self-efficacy, as one of the concepts of empowerment model, plays a role in increasing the caring behavior. Accordingly, the present study aimed to evaluate the effect of educational intervention based on self-efficacy theory on the caring behavior of mothers having children with cancer. Methods This before-after clinical trial study was conducted on all mothers (N = 86) of children with cancer undergoing chemotherapy who referred to Bandar Abbas Children's Hospital. All mothers participate in fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…Concerning, studied mother's self-efficacy, the current study illustrated that, less than one third of studied mothers had low self-efficacy level at pre family empowerment implementation, while, majority of studied mothers had high self-efficacy at post and after three months of family empowerment implementation. This study accordance with Barani, et al (2021) (40) , who studied " effect of educational intervention based on self-efficacy theory on the caring behavior of mothers having children with cancer " and found that, a significant difference in the mean score of mothers' self-efficacy after intervention (P < 0.001). Besides, the twoway self-efficacy score of the first and second follow-ups was p = 0.096.…”
Section: Third Step: (Process Evaluation)supporting
confidence: 90%
“…Concerning, studied mother's self-efficacy, the current study illustrated that, less than one third of studied mothers had low self-efficacy level at pre family empowerment implementation, while, majority of studied mothers had high self-efficacy at post and after three months of family empowerment implementation. This study accordance with Barani, et al (2021) (40) , who studied " effect of educational intervention based on self-efficacy theory on the caring behavior of mothers having children with cancer " and found that, a significant difference in the mean score of mothers' self-efficacy after intervention (P < 0.001). Besides, the twoway self-efficacy score of the first and second follow-ups was p = 0.096.…”
Section: Third Step: (Process Evaluation)supporting
confidence: 90%
“…Based on previous studies, people with high SEEF have more behavioral stability and self-confidence than people with low SEEF (11,12). Self-efficacy is considered one of the essential structures of behavioral theories, which plays a vital role in health promotion (13,14).…”
mentioning
confidence: 99%